Beleidsregel Dinas Perdagangan dan Perindustrian dalam Mengoptimalkan Pasar Rakyat Tualang Tahun 2018 - Wulan Dari; Adlin Adlin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The writing of this scientific article raises the phenomenon that occurs in the Tualang District community in the process of enforcing Circular No. 511.2/DPP/PSR/IX/2018/200 in relocating street vendors from the edge and shoulder of the KM 4 highway in front of Tuah Serumpun Market to Tualang People's Market in 2018. This problem can be analyzed using the theory of requirements that must be met in the manufacture of beleidsregel Van Kreveld (quoted by Indroharto in Ridwan HR, 2007) and the application/enforcement of the regulations of Ridwan HR (2007) as well as by using the theory of factors influencing law enforcement Soerjono Soekanto (2008). The results of this scientific article show that Circular No. 511.2/DPP/PSR/IX/2018/200 has met the requirements that must be met in the manufacture of beleidsregels. However, in terms of implementation, the circular has not fully met the required requirements. The factors that hinder the enforcement of circulars include law enforcement factors, facilities and facilities factors, community factors, and cultural factors. Meanwhile, legal factors do not hinder the enforcement of the circular.